2009
DOI: 10.1080/01612840802601408
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Relationship Between Mental Health Professionals and Family Caregivers: Has There Been Any Change?

Abstract: A number of international studies have highlighted family caregivers' (FCGs') dissatisfaction with their relationship with mental health professionals (MHPs) when providing care for mentally ill family members. However, few studies have explored the mental health professionals' perspective of this relationship. This study explored both FCGs' and MHPs' perspectives. Semi-structured interviews were conducted with seven FCGs and seven MHPs from two different geographical areas of New Zealand. Thematic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
3
18
0
3
Order By: Relevance
“…A study from New Zealand (Nicholls & Pernice, 2009) confirmed results from studies in Sweden and the US that relatives had problems collaborating with mental health personnel. The ability to communicate is essential for cooperation to occur.…”
Section: Relatives' Experiences With Mental Health Servicessupporting
confidence: 74%
See 1 more Smart Citation
“…A study from New Zealand (Nicholls & Pernice, 2009) confirmed results from studies in Sweden and the US that relatives had problems collaborating with mental health personnel. The ability to communicate is essential for cooperation to occur.…”
Section: Relatives' Experiences With Mental Health Servicessupporting
confidence: 74%
“…Although some relatives in our study reported that they felt health personnel hindered the relatives' attempts at cooperation, Andrew, Farhall, Ong, and Wadell (2009) found that professionals and caregivers each held the other responsible for achieving collaboration. One study found incongruence between health personnel's intentions to foster a positive collaboration and relatives' negative experiences (Nicholls & Pernice, 2009). The present study shows that relatives experienced that health personnel expected them to follow up on the mentally ill person even without cooperation.…”
Section: Relatives' Experiences With Mental Health Servicesmentioning
confidence: 97%
“…Research concerning the relationship between the family members of people with mental health problems and their professional caregivers has shown several problems indicating dissatisfaction and difficulties in this relationship (Ferriter & Huband, 2003; Nicholls & Pernice, 2009; Rapaport, Bellringer, Pinfold, & Huxley, 2006). Family members report experiences of contacts with personnel that were too brief and infrequent, lack of communication, and not being listened to (Ferriter & Huband, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A commonly recognized difficulty to implement evidence-based research into practice is that implementing new interventions often take much time. They require changes in working routines that are often confronted with resistance and challenges [51]. Translating research evidence into every day work is recognized as difficult [52].…”
Section: Discussionmentioning
confidence: 99%